SOCIO-ECONOMIC EFFECTS OF COVID-19 PANDEMIC ON THE NIGERIA WORKING CLASS - UZOH, Bonaventure Chigozie (Socialscientia: Journal of Social Sciences and Humanities, 2021)
The outbreak of COVID-19 in Wuhan, China in November 2019, and its subsequent spread to the rest of the world have affected the global community in deleterious ways. It has resulted in deaths and infirmity on the parts of those affected by the virus. Its lethality has engendered a global lockdown forcing people to stay in their homes in order to stem the rapid spread of the virus. This has correspondingly affected the economies and social life in affected countries. Indeed, Job losses, wage cuts, and outright closure of some businesses have been rampant. This paper, therefore, examines the social and economic effects of the COVID-19 pandemic on the Nigerian working class. The analysis is hinged on the social dislocation and normalization process theories. The paper argues that the post-pandemic future is bleak and uncertain for the working class, and indeed all Nigerians because of the foreseeable durability of the pandemic. The paper then recommends that the Nigerian government should provide leadership in implementing policies that will help to alleviate the suffering of the Nigerian working people. It suggests that such policies should include saving jobs and strengthening the Micro, Small, and Medium Enterprises (MSMEs) with credit facilities.